Financial Development and Economic Growth : An Economic Analysis for Singapore - Leigh, Lamin (IMF Working Papers; Working Paper ;, 1996)
With the emergence of the rapidly expanding literature on endogenous growth, the relationship between financial development and economic growth has received a new source of inspiration. Recent cointegration techniques that focus on the estimation and the identification of long-run economic relationship(s) between data variables are particularly appropriate to the study of long run endogenous growth models. This paper has applied these techniques to the Singapore data using a supply-side framework. By and large, the econometric analysis in this paper has yielded results that are in line with predictions of endogenous growth models. In particular, we find that financial development positively affects both transitional and long-run growth in Singapore.